Experimental strabismus surgery using triamcinolone: outcomes and effects on inflammatory response - Carvalho,Luis Eduardo Morato Rebouças de (2007)
PURPOSE: To evaluate the efficiency of triamcinolone (TRI) in limiting the postoperative inflammatory response and scarring after strabismus surgery. METHODS: A prospective, two-stage, masked, controlled trial was conducted. In the first stage, the inflammatory response at the extraocular muscle reattachment site was analyzed after superior rectus recession in ten rabbits. In the second stage, TRI (40 mg/ml) was applied during surgery to the eyes of 16 rabbits with superior rectus recession. As a control, contralateral eyes were treated with physiological saline. Fifteen days later, exenteration was performed, and the sites of muscle reattachment were processed for histological examinations. The sums of the areas of the granulomas in the extraocular muscle reattachment sites of control and treated eyes were compared. RESULT: There was a preliminary inhibition effect of TRI on the inflammatory response of treated eyes compared with that of control eyes. CONCLUSIONS: In the conditions of conducting this study the introperative use of TRI was effective in controlling the postoperative inflammatory response in rabbit eyes after extraocular muscle surgery.